1983
DOI: 10.1021/i300012a020
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of synfuels from oil shale. 3. Studies with actual shale-derived middle distillates

Abstract: The storage stability of various middle distillate fuels derived from oil shale was investigated by means of an accelerated storage stability test. A variety of liquids were studied including crude shale oils boiling in the middle distillate range, partially upgraded shale oils, and severely refined fuels. Large amounts of sediment were obtained from liquids with high heteroatom content. However, no direct correlation between nitrogen, sulfur, no oxygen levels and sediment level was observed. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…This explanation must apply to many fuels; when it does, the fuel stability should be improved as the reactive components are consumed, and examples have been reported (Bowden and Brinkman, 1980;Stavinoha and Brinkman, 1981). Some nitrogen and sulfur compounds increase deposit formation and some do not (Frankenfeld et al, 1983). The considerable recent literature on deposits from 2,5-dimethylpyrrole in fuels shows mostly that this compound is unusually reactive in oxidation and that its oxidation product is unusually insoluble.…”
Section: (5)mentioning
confidence: 99%
“…This explanation must apply to many fuels; when it does, the fuel stability should be improved as the reactive components are consumed, and examples have been reported (Bowden and Brinkman, 1980;Stavinoha and Brinkman, 1981). Some nitrogen and sulfur compounds increase deposit formation and some do not (Frankenfeld et al, 1983). The considerable recent literature on deposits from 2,5-dimethylpyrrole in fuels shows mostly that this compound is unusually reactive in oxidation and that its oxidation product is unusually insoluble.…”
Section: (5)mentioning
confidence: 99%
“…The difficulty of removal of nitrogen from pyrrole-types has also been noted by other workers (Ford et al, 1981;Holmes and Thompson, 1983). The resistance to HDN of pyrrolic compounds is important as these compounds are known to produce fuel instability (Frankenfeld et al, 1983).…”
Section: Chemical Characterization Of Hydrotreated Oilmentioning
confidence: 99%
“…They concluded that 1 year of ambient storage should make little difference in the refining process used to upgrade the crude oil. Frankenfeld et al found that for crude and partially refined shale distillates the nitrogen content is not a general predictor of fuel storage stability, although a rough correlation exists between nitrogen content for fuels from the same shale source and with similar processing histories (Frankenfeld et al, 1983c).…”
Section: Introductionmentioning
confidence: 99%